Real-world assessment of an integrated clinical model on oral hepatitis C therapy at Southern Ohio Medical Center. (3rd September 2019) - Ferraro, Robert; Quillen, Stephen; Phillips, Rory; Newman, Brandon
Abstract: Background: The area and population served by the Southern Ohio Medical Center (SOMC) is one that has been hit hard by the opioid epidemic, resulting in a very high incidence of Hepatitis C virus infected individuals. In this rural area, many patients have struggled with access to specialty healthcare. In January 2018, specialty pharmacy services were started. The main goals were to provide a valuable and personalized service to patients and increase access to specialty medications. When taken as prescribed, HCV therapies can lead to high cure rates (>95%). The program integrated a clinical pharmacist and pharmacy liaison in the infectious disease clinic to begin providing in-clinic education, 24/7 support, prior authorization assistance, financial aid assistance, refill reminders, and other services to patients. The specialty pharmacy service has assisted many local patients to obtain treatment for HCV. The following data analysis details the study design and results. Aims: The study was completed to assess the impact of the clinic-based specialty pharmacy program on medication access, affordability, and clinical outcomes for patients with HCV. Methods: The study was IRB-approved. Endpoints measured were SVR12 rates, rates of patient return for SVR12 labs, and out-of-pocket costs for patients using the SOMC Specialty Pharmacy. To be eligible for the study, patients must have started an HCV regimen written by an SOMC provider after January 1, 2018. Data was collected by reviewing patient electronic medical records and pharmacy dispensing records. Results: The study included 67 HCV patients who utilized the SOMC specialty pharmacy program to obtain treatment. Thirty-seven of the patients were male, none had liver decompensation, and 65 were treatment-naïve. By offering in-clinic specialty pharmacy services to patients, SOMC was able to remove barriers, such as cost, to improve specialty medication access and adherence. This resulted in 100% medication access and therapy completion rates for participating patients. SVR12 rates were higher than clinical trials. Finally, the average out of pocket cost to patients was found to be $0.75, with 90% of patients having zero copay. Clinical pharmacists and pharmacy liaisons played a key role in achieving this result by providing in-person education to patients, securing financial assistance for patients, and regularly following-up with patients regarding their therapy. Conclusions: Clinic-based health system specialty pharmacy programs can play a vital role in improving medication access and adherence, leading to better clinical outcomes. By offering on-site specialty pharmacy services, SOMC provides a personalized patient experience and affordable access to specialty prescriptions. These elements help ensure patients adhere to their treatment regimens over time and fully realize the benefits of their specialty medications.